The Meaning of “Independent Learning” in Curriculum Planning under the Merdeka Curriculum at the Senior High School Level - Maulana Iqbal Mahendra; Daud Hizbalhaq Addamawi; Andryan Verly Dwi Pratama; Irwan Efendi; Gina Muta'affif (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
A significant educational revolution in Indonesia, the Merdeka Curriculum is intended to address the learning crisis and fulfill the needs of 21st-century skills. The execution of this curriculum at the senior high school (SMA) level faces particular difficulties due to the developmental characteristics of students and the growing complexity of subject specialisation. With a special emphasis on lesson module creation, diagnostic assessment, and the Project for Strengthening the Pancasila Student Profile, this study seeks to examine how the idea of